Role of Internet slogans in the political discourse of modern Runet - Zykova E. I. (Interactive science, 2017)
this article analyzes the functioning of the Internet in the modern Runet slogans, as well as the definition of their role in the political discourse of language as an effective means of manipulating public consciousness. The analysis shows that in Runet among numerous idiomatic means of expression were specific slogan to the online space, which carry socially significant meaning. These Internet slogans are insulated public opinion, civic position that undoubtedly debarking of the most powerful means of social influence and social manipulation.
Keywords: фразеология; политический дискурс; phraseology; political discourse; крылатые слова; политические лозунги; хэштеги; трансформа; winged words; political slogans; hashtags; transformer